1986
DOI: 10.1148/radiology.161.3.2947262
|View full text |Cite
|
Sign up to set email alerts
|

Side branch occlusion complicating percutaneous transluminal coronary angioplasty.

Abstract: A frequent concern during angioplasty is the possibility of occluding important side branches that originate in arterial stenoses subjected to balloon dilatation. The effect of dilatation on 93 side branches (greater than or equal to 1 mm in diameter) was evaluated in 86 patients undergoing percutaneous transluminal coronary angioplasty (PTCA) in whom those branches arose directly in dilated segments of the left anterior descending, circumflex, or right coronary arteries. Seventy-six of the 93 side branches ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
11
1

Year Published

1992
1992
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 0 publications
1
11
1
Order By: Relevance
“…2 The current study confirmed that side branches with ≥50% ostial stenosis were at higher risk for occlusion than those without ostial stenosis. Since the beginning of the stent era, stent implantation in coronary lesions involving side branches has been recognized as a potential source of acute complications.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…2 The current study confirmed that side branches with ≥50% ostial stenosis were at higher risk for occlusion than those without ostial stenosis. Since the beginning of the stent era, stent implantation in coronary lesions involving side branches has been recognized as a potential source of acute complications.…”
Section: Discussionsupporting
confidence: 78%
“…. [1][2][3][4][5] Meier et al were among the first to identify the risk of side branch occlusion associated with parent vessel angioplasty. 1 They emphasized that side branches involved in vessel narrowing are at high risk for side branch occlusion during PCI.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports have shown that significant stenosis at the SB ostium is an important predictor of SB occlusion after bifurcation PCI [35][36][37]. However, stenosis severity and diameters of the MB or SB had minimal influence on selection of PCI strategy in the present study.…”
Section: Discussioncontrasting
confidence: 61%
“…When there is extensive atheromatous plaque affecting the SB ostium, plaque shift may be more importantly involved in the development of SB complication. Actually, previous studies with a bare metal sent or a drug-eluting stent have shown that SB with at least 50% ostial stenosis was a higher risk for occlusion than those without ostial stenosis [16,17].…”
Section: Discussionmentioning
confidence: 99%